Погляд на множинні розподіли через модифіковані комбінанти - Rybczyński, M.; Wilk, G.; Włodarczyk, Z. (Publishing house "Academperiodika", 2019)
The experimentally measured multiplicity distributions exhibit, after a closer inspection, the peculiarly enhanced void probability and the oscillatory behavior of modified combinants. We show that both these features can be used as additional sources of information, not yet fully explored, on the mechanism of multiparticle production. We provide their theoretical understanding within the class of compound distributions.